PEMBERDAYAAN PEMERINTAH DESA DALAM RANGKA PELAYANAN MASYARAKAT DI KECAMATAN TABUKAN UTARA KABUPATEN SANGIHE - MARKUS, MICHAEL JOOTH; SONDAKH, TELLY; LALOMA, ALDEN (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: less attention from the Government in considering the subdistrict aspirational society and in meeting the needs ofcommunities make communities living in poverty. Based on the background of the objectives in this research is toknow how the Government's empowerment villages in district North Tabukan District Sangihe, performance andeffectiveness in order to provide the service.Research methods used in this research is descriptive qualitative. Method of collecting Data through: interviews,documentation, the stages of data analysis that explains the stages of analysis on the research of Qualitative Deskritif, asfollows: reduction of data (data reduction), the presentation of the Data, draw conclusionsThe results showed the Government's Empowerment villages in district North Tabukan still hasn't been fullest it is causeddue to the lack of Government attention to the village against society. So what is the needs of the community are not in theknow by the Government of the village.Keywords: Empowerment, service, Government of the village